2023
DOI: 10.5089/9798400235436.001
|View full text |Cite
|
Sign up to set email alerts
|

Global Supply Chain Disruptions: Challenges for Inflation and Monetary Policy in Sub-Saharan Africa

Abstract: IMF Working Papers describe research in progress by the author(s) and are published to elicit comments and to encourage debate. The views expressed in IMF Working Papers are those of the author(s) and do not necessarily represent the views of the IMF, its Executive Board, or IMF management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Recent studies that quantify aggregate losses in this context include Attinasi et al (2023), Felbermayr et al (2023, Javorcik et al (2022) and others. 4 Most related and complementary to our analysis are Fally and Sayre (2018) and Bolhuis et al (2023), who show that the specific features of commodities amplify the aggregate effects of trade disruptions in multicountry, multisector trade models. Bachmann et al (2022), Chepeliev et al (2022), Di Bella et al (2022, Albrizio et al (2023) and others focus on the implications of supply disruptions to natural gas and oil markets mostly based on second order approximations derived from multicountry multisector trade models.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Recent studies that quantify aggregate losses in this context include Attinasi et al (2023), Felbermayr et al (2023, Javorcik et al (2022) and others. 4 Most related and complementary to our analysis are Fally and Sayre (2018) and Bolhuis et al (2023), who show that the specific features of commodities amplify the aggregate effects of trade disruptions in multicountry, multisector trade models. Bachmann et al (2022), Chepeliev et al (2022), Di Bella et al (2022, Albrizio et al (2023) and others focus on the implications of supply disruptions to natural gas and oil markets mostly based on second order approximations derived from multicountry multisector trade models.…”
Section: Introductionmentioning
confidence: 80%
“…Starting from the methodology of Fally and Sayre (2018) and updated by Bolhuis et al (2023), we create the new dataset with several key innovations. First, we develop a set of adjustment factors to correct for different unit measurements for mineral commodities in the ©International Monetary Fund.…”
Section: A New Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, food prices in SSA have risen substantially over the years (Bolhuis & Kovacs, 2022;Okou et al, 2022). Headey (2016) revealed that the implications of the rise in food prices on poverty may be negative or positive.…”
Section: Introductionmentioning
confidence: 99%